Pain in Perspective - Ghosh, Subhamay (IntechOpen, 2012)
Pain has been there since man has existed and whatever the method or technique of its relief, if successful will always lead to a special place in the heart of the person receiving it and also to the person delivering it. "Pain in Perspective" takes us into a journey of how it all began and then leads us to understand the various concepts of pain relief today. From musculoskeletal pain to complex shoulder pain and from neurological examination to charting out pain, this book describes new ideas and latest descriptions of pain concepts and their treatment.